A Preliminary Evaluation of Plasma B-Type Natriuretic Peptide as a Screening Test for Left Ventricular Diastolic Dysfunction in Non-Cardiac Intensive Care. Issue 5 (September 2013) - Sturgess, D. J.; Parmar, D.; Dulhunty, J. M.; Hegde, R.; Jarrett, P.; Udy, A.
Left ventricular filling and thus diastolic function are frequently monitored and managed in critical care. However, scant data exist regarding possible screening tests for diastolic dysfunction in the intensive care unit (ICU). The present study aimed to evaluate plasma b-type natriuretic peptide (BNP) as a marker of diastolic dysfunction in a single-centre cohort of 'non-cardiac' ICU patients. The ICU is non-cardiac in that it provides mixed medical/surgical services with the exception of cardiology, cardiac surgery and solid organ transplantation. Clinical data were recorded over the first 24 hours of ICU stay for 32 consecutive patients. Transthoracic echocardiogram and blood collection for BNP assay were then performed. Diastolic dysfunction was demonstrated in 34% (n=11). Mean ± standard deviation BNP values were higher with diastolic dysfunction (238±195 vs 72±78 pg/ml; P =0.003). A BNP threshold of >43 pg/ml yielded a sensitivity of 80% and a specificity of 59%; area under the receiver operating characteristic curve was 0.82. BNP correlated independently with E/e' (R = 0.425; P =0.015) (E/e': peak early transmitral velocity [E]/early diastolic mitral annular velocity [e']) but not left ventricular ejection fraction ( P =0.8), illness severity (Acute Physiological and Chronic Health Evaluation II; P =0.3) or fluid balance ( P =0.4). Diastolic dysfunction was common in this cohort of non-cardiac ICU patients and was independently associated with a significantly higher BNP. The potential application as a screening test for diastolic dysfunction is likely to require a threshold lower than previously proposed for heart failure.